Evaluasi Program Pendidikan Jarak Jauh Berbasis Tuweb Studi di Tobelo, Maluku Utara - Mohbir Umasugi (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to evaluate the implementation of distance education program based on webinar tutorial (Tuweb) during the Covid-19 pandemic. The focus of the evaluation was on the learning group (Pokjar) Tobelo, North Halmahera Regency. Descriptive qualitative approach was used as a method to explain the evaluation of Tuweb implementation in the field. By using documentation study and interview techniques, various data can be collected and analyzed in stages through data reduction, data presentation, and conclusion drawing. The results of this study indicate that the Tuweb model is very helpful for students in carrying out lectures during the Covid-19 period. Because students can interact directly with each other and with tutors through the MSTeams application provided by Open University. However, there are various obstacles that hamper the implementation of Tuweb such as internet network disturbances, power outages during the tutorial process, and the location of students' residence which is far and not yet connected to wifi